PENERAPAN MODEL PEMBELAJARAN ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, AND SATISFACTION) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA - Nur Ismiyati (De Fermat : Jurnal Pendidikan Matematika, 2019)
This research is a classroom action research that aims to improve mathematics learning in class VIII Junior High School 1 at Bontonompo through the ARIAS learning model. The problem in this research are less then 75% of students have mathematics learning under KKM and students less learning activites. The research was carried out during two cycles. The obtained data were analyzed qualitatively and quantitatively. Based on the results of the research in Cycle I, only 26% of students fulfilled the KKM value were continued to Cycle II and the results met individual and classical completeness is 78% of students fulfilled KKM scores and student activities increased. Keywords : ARIAS Learning Model, Activity, Learning Outcomes